The Scheduling System of Civil Aviation Based on Web-Based Aviation Safety Regulation - Honggowibowo, Anton Setiawan; Retnowati, Nurcahyani Dewi; Wiyono, Koko (SENATIK STT Adisutjipto, 2019)
Cabin crew scheduling in the world of flight must be made very carefully. Because in making cabin crew scheduling there are several requirements that must be met by the scheduling officer such as flight time, cabin crew working hours and rest hours. In making the scheduling it takes a long time because the scheduling officer must ensure the cabin crew's duties in carrying out their duties do not exceed or violate these requirements. Therefore, a cabin crew scheduling system was created to assist schedulers in making cabin crew scheduling using PHP and Oracle databases. This scheduling system is designed to be able to calculate flight time, cabin crew working hours and cabin crew rest time so that scheduling officers no longer have difficulty synchronizing these requirements so that cabin crew officers do not violate these requirements with just one step in the process. This system succeeds in doing 9 Minutes 50 Seconds faster than doing it manually in making just 1 flight route. The time difference can be greater if in 1 day there are more than 1 flight route.